Analysis of vibration characteristics of gear system during start-stop process - TU Wenbing; HU Dengliang; WANG Hao; LIU Chenlu; CAO Zheng (Jixie qiangdu)
When the gear system starts or stops in non-stationary working conditions, a sharp change of the speed can cause it to exhibit complex vibration characteristics which has a significant impact on the performance and lifespan of the gear. Considering the influence of time-varying meshing stiffness, backlash and gear meshing error, a dynamics model of spur gear system was established. The influence of external load and angular acceleration on the vibration characteristics of the start-stop process was studied. At the same time, the time-frequency analysis of the non-stationary vibration signal of the gear system was carried out by using the short-time Fourier transform. The results show that increasing the load and angular acceleration during the start and stop processes will exacerbate the degree of vibration and impact of the gear pair, and both will make the unstable motion process in the early start period end earlier, and the unstable motion process in the late stop period appear later, but the impact components in the late start period (the early stop period) will increase (decrease). In the frequency domain, increasing the external load will enhance the energy of the harmonic component of the gear system’s meshing frequency, but it has no effect on the fundamental energy of the meshing frequency. However, increasing the angular acceleration will enhance the energy of both the fundamental and harmonic components of the meshing frequency.